High-temperature binding parameters and molecular dynamics of 4-hydroxybenzoic acid and β-casein complexes, determined via the method of continuous variation and fluorescence spectroscopy. (May 2021) - Condict, Lloyd; Hung, Andrew; Ashton, John; Kasapis, Stefan
Abstract: Interactions between β -casein and 4-hydroxybenzoic acid (4HBA) were investigated following ultra-high temperature (UHT) treatment at 140 °C for 10 s. The aim of the work was to identify the binding strength, binding stoichiometry and type of molecular interactions between protein and bioactive compound. Molecular dynamics (MD) analysis shows that binding is stabilised by a wider variety of residues than is often indicated in simpler docking studies. Construction of Job plots via fluorescence quenching argues that β -casein can accommodate two 4HBA molecules. This is in agreement with MD analysis, which demonstrates the stability of ligand in two different binding sites of the receptor. FTIR results indicate a binding interaction between the two components and UV–vis measurements record an increase in the absorption of 4HBA following UHT treatment in the presence of β -casein. The latter observation argues that 4HBA may be bound covalently following heat treatment. This is further supported by MD simulations and quantum mechanics calculations that indicate one site has the potential for binding covalently to 4HBA via the lysine32 residue of the β -casein molecule. This work addresses often overlooked issues in the determination of binding parameters, through the use of the method of continuous variation for the accurate determination of binding stoichiometry, as well as making use of a nonlinear fluorescence binding equation to account for the residual fluorescence of formed complexes. The findings give a broader understanding of the fate of bioactive ingredients in UHT treated beverage systems, allowing industry to make informed decisions on the inclusion of insoluble fibres and the impact of heat treatment on their products. Graphical abstract: Image 1 Highlights: β -casein with 4-hydroxybenzoic acid solutions were analysed following UHT treatment. Two binding sites were identified via molecular docking and Job plot analysis. UV–vis analysis indicates a covalent interaction between protein and phenolic acid. In silico methods indicate covalent binding between 4HBA and lysine32 of β -casein.